Rural Education and Online Teaching in Wrestling with the Covid-19 Pandemic - Abigail, Dan-Mallam Yakubu; Godswill Ejeohiolei, Esechie; Siti Zanariah, Ahmad Ishak (Macrothink Institute, 2022)
Education is wise, hopeful, and respectful cultivation of learning and change is undertaken in the belief that we all shall have the chance to share in life. Education is necessary for each and everyone in order to improve knowledge, way of living as well as social and economic status in life. It also plays a fundamental role in our career growth as well as in personal growth. However, despite the fact that education is important for human development, rural education receives less attention from the government in its reform agenda. This may be because the education Ministry is usually located in urban areas. This lack of attention from the government has produced several setbacks to the development of rural education, starting from poor infrastructures, lack of qualified teachers to inadequate laboratories and libraries. Based on these problems, it can be said that rural students may not be able to compete with their counterparts in urban schools.